International Conference on Ground Anchorages and Anchored Structures in Service 2007 : proceedings of the two day international conference organised by the Institution of Civil Engineers and held in London on 26 and 27 November 2007 - Littlejohn, G. S. (Thomas Telford, 2008)
This title shows how routine inspection and monitoring can extend the service life of the anchored structures that represent key elements of a country's infrastructure.
Keywords: Anchorage (Structural engineering) -- Congresses.; elektronické knihy; electronic books